Illustrated guide to the National Electrical Code - Miller, Charles R. (Brooks Cole / Thomson Learning, 2005)
Miller combines years of experience as an electrical contractor and a trainer in producing the second edition of this guide to the National Electrical Code(r) (NEC(r)). Designed to teach through visualization, the text contains over 600 technically precise, highly detailed illustrations to explain--and minimize misinterpretation of--the NEC requirements. For the second edition, the text has been thoroughly updated to reflect the requirements of the 2005 NEC.